2012
DOI: 10.1002/ptr.4844
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Microbial Activity and Composition of Manuka and Portobello Honey

Abstract: Recently renewed interest in the therapeutic properties of honey has led to the search for new antimicrobial honeys. This study was undertaken to assess the antimicrobial activity and composition of a locally produced Portobello honey (PBH) on three bacteria known to infect wounds. Manuka honey (MH) was used for comparative purposes. Broth culture and agar disc diffusion assays were used to investigate the antimicrobial properties of honey. The honeys were tested at four concentrations: 75%, 50%, 10% and 1% (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 34 publications
3
54
0
1
Order By: Relevance
“…Since the 1990s, research on honeys has regained momentum, with focus towards antibacterial properties particularly against bacteria associated with antibiotic-resistance and infected wounds [35]. This has led to approval for use of manuka honey in the treatment of infected wounds, burns, and ulcers [69].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s, research on honeys has regained momentum, with focus towards antibacterial properties particularly against bacteria associated with antibiotic-resistance and infected wounds [35]. This has led to approval for use of manuka honey in the treatment of infected wounds, burns, and ulcers [69].…”
Section: Introductionmentioning
confidence: 99%
“…In a trial comparing the anti-oxidant activity of manuka honey with acacia honey from Germany and wild carrot honey, the former was deemed superior in its phenolic content (899.09 mg gallic acid/kg). 21 It was observed that manuka honey has significantly higher levels of the polyphenols and antioxidant activity than portbello honey (a honey made in Edinburg, UK) 1 Even though trials have been conducted on total antioxidant content of the honey, and respective clinical outcomes, further research needs to be conducted. Determination of the specific therapeutic role of the anti-oxidants and co-factors in manuka honey may reveal synergistic activities.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…1,2,3,4 Manuka honey is used both internally and externally. It is marketed as a gel for topical applications (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, researchers at Queen Margaret University, Edinburgh, Scotland reported the antimicrobial activity of a Scottish Honey called Portobello Honey 22 . Portobello Honey was produced by honey bees in an apple orchard in Portobello, Edinburgh, Scotland.…”
Section: Accepted Manuscriptmentioning
confidence: 99%